Two New Species of Black Flies (Diptera: Simuliidae) from the High Andes of Colombia - Mantilla, Juan S.; Moncada, Ligia I.; Matta, Nubia E.; Adler, Peter H. (Zootaxa, 2013)
The females, males, pupae, and larvae of two new species of Simulium are described and illustrated from a small stream 3950 m above sea level in the Lake Otún area of the Colombian Andes Mountains. Simulium (Pternaspatha) quimbayium n. sp. represents a 630-km northeastern extension of the distributional range of previously known members of the subgenus Pternaspatha, and Simulium (Psilopelmia) machetorum n. sp. represents the highest altitude recorded for a species of the subgenus Psilopelmia. These species illustrate the unique simuliid biodiversity in the páramo ecosystem of the high northern Andes.